2010
DOI: 10.1089/cell.2009.0079
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and Characterization of Human Embryonic Stem Cell-Derived Osteoblast-Like Cells

Abstract: Human embryonic stem cells (hESCs) have the potential to serve as a repository of cells for the replacement of damaged or diseased tissues and organs. However, to use hESCs in clinically relevant scenarios, a large number of cells are likely to be required. The aim of this study was to demonstrate an alternative cell culture method to increase the quantity of osteoblast-like cells directly derived from hESCs (hESCs-OS). Undifferentiated hESCs were directly cultivated and serially passaged in osteogenic medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…In vitro osteogenic differentiation of primary osteoblasts [8][9][10][11][12][13]44] and ESCs [17][18][19][20][21] have both been well described, but there have been few comparative studies. In this study, both cell types showed expression of markers indicative of osteogenic differentiation and formed nodules comprising Values corrected to proportion of osteogenic control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro osteogenic differentiation of primary osteoblasts [8][9][10][11][12][13]44] and ESCs [17][18][19][20][21] have both been well described, but there have been few comparative studies. In this study, both cell types showed expression of markers indicative of osteogenic differentiation and formed nodules comprising Values corrected to proportion of osteogenic control.…”
Section: Discussionmentioning
confidence: 99%
“…Both mouse [17,18] and human ESCs [19][20][21] have been shown to display the features of osteogenically differentiated cells in vitro, exhibiting molecular and structural features resembling bone tissue by the formation of mineralized bone nodule structures. The majority of osteogenic protocols for ESCs direct cell differentiation by including factors in the culture medium, such as b-glycerophosphate (BGP), ascorbate, dexamethasone, simvastatin, retinoic acid, vitamin D 3 , and bone morphogenic proteins [3,[22][23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%
“…20 Previous to implantation, the differentiation conditions for committing MAPCs to osteoprogenitor cells in vitro have required long culture periods, as in differentiation of human embryonic stem cells into mesenchymal Color images available online at www.liebertpub.com/tea precursors. 5,[40][41][42] However, to satisfy the demand of high osteoprogenitor cell numbers to regenerate large skeletal defects via a tissue-engineered approach, novel aggregate culture conditions were used here to assure a consistent MAPC osteogenic differentiation on a large scale. 17 More than 1000 progenitor cells/cm 3 have been required for bone healing to occur.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of attempts to generate osteo-and chondroprogenitors (also known as bone marrow-derived mesenchymal stem cells [MSCs]) from embryonic stem cells (ESCs) [1][2][3][4][5][6][7][8][9][10] and iPSCs [11][12][13][14]. However, there are three broad limitations in performing these types of studies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reliant on EBs are limited by variability and substitute a black box for a true mechanistic understanding of differentiation processes. Third, although bone formation can be assayed with great specificity by in vivo transplantation, many studies that do so are limited by an incomplete collection or presentation of data or analysis of the results [5,10,13,[18][19][20][21][22][23][24]. Thus, reports on the formation of bone or cartilage from donor cells are sometimes premature based on the evidence presented.…”
Section: Introductionmentioning
confidence: 99%